Development and evaluation of a sorghum tisane - Dodd, Angela Lynn (Kansas State University, 2010)
Known for its antioxidant activity and other health benefits, tea is the second most consumed beverage in the world, following water. With up to 6% (w/w) of phenolic compounds, sorghum has the highest content compared to other cereals. The objective of this research was to develop and analyze a sorghum tisane using two different red sorghum hybrids. Tisanes are herbal infusions composed of anything other than the leaves from the Camellia sinensis plant. The sorghum kernel was cracked using an Allis experimental roll stand equipped with a Le Page cut mill. Samples were sifted at 180 RMP- 4” diameter throw for 2 min. The two hybrids were roasted in a Whirlpool convection oven at 212°C for 13 or 15 min. Three fruit and herbal combinations were tested to increase consumer acceptability. Samples was brewed for 4 min in 8fl.oz at 100°C. Oxygen Radical Absorbance Capacity(ORAC) and Total Phenolic Content (TPC) were used to analyze the beverage along with chemical, physical and sensory tests. TPC results showed sorghum tisane to have 38.5±6.91 mg gallic acid equivalence/ 8fl oz. and 433.7 ±7.11 μM Trolox equivalence/ 236.6 mL (8 fl.oz, 1 cup) for an ORAC value. Fruit and herbal combinations were also added to the sorghum to increase overall consumer acceptability. These combinations included strawberry mixed with lemon, blood orange mixed with pear, and pineapple mixed with orange. A consumer acceptance test was performed on the three different sorghum tisanes using a 9 point hedonic scale. Results showed an overall acceptability at 6.63±1.54 for the sorghum tisane infused with a strawberry and lemon combination while the sorghum tisane with pineapple orange scored 6.72 . These results demonstrate the potential for introducing a consumer acceptable sorghum tisane into the market.
Keywords: Sorghum; Tisane; Grain tea; Agriculture, Food Science and Technology (0359)